CONSUMER BEHAVIOR IN THE PERSPECTIVE OF CONVENTIONAL ECONOMICS AND ISLAMIC ECONOMY - Pepe Iswanto; Yani Mulyani; Husna Lailatul Qadar (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
Consumer behavior in the perspective of conventional economy is based on the philosophy of capitalism, so that each individual is more rational than spiritual. While in the perspective of Islamic economics, consumer behavior is based on the philosophy of God so that in every activity to meet the needs of consumers are required to always be guided by the principles of monotheism, khilafah, and also justice. In addition the authors find the existence of similarities and differences from both perspectives of the theory. The similarity between consumer behavior in carrying out consumption activity in conventional economics and Islamic economy there are three, among them in terms of understanding, philosophy base, motivation and purpose of consumption, and consumer behavior theory. The difference lies in the foundations of philosophy, the principles of consumption, the motives and purposes of consumption, the configuration of consumer needs, and the latter lies in consumer behavior. This study was conducted with the aim to know: (1) consumer behavior in conventional economic perspectives (2) consumer behavior in sharia economic perspective (3) comparison of consumer behavior in conventional economic and economic perspectives of sharia. This research method uses library research approach, because the object of study is focused on the study by conducting a review study on books, data, literatures related to the analysis of research discussion related to consumer behavior, both in economy conventional and Islamic. The results show that: (1) Consumer behavior involves the behavior of consumers, where they can illustrate the search to buy, use, evaluate and improve a product and their services. (2) The consumption behavior of Islam based on the guidance of the Qur'an and Hadith needs to be based on an enhanced rationality that integrates belief in truth that transcends this very limited human rationality. (3) Comparisons between consumer behavior in conventional economics and the declining Islamic economy, explains that there are some differences from both points of view. The first is lies in the cornerstone of the philosophy of consumer behavior. Second, related to the principle of consumption. The principle of consumption in the conventional economy there are three namely freedom, self interest, and material. Third, look at the motive and purpose of consumption